Determinan keputusan pembelian rumah sederhana di Kota Palembang - Maya Fusfita; Saadah Yuliana; Imelda Imelda (Jurnal Ekonomi Pembangunan, 2018)
The development will be the needs of the house continue to increase due to the increasing number of population. Therefore, the needs of the development of a simple home shown to low income people that done by the government through the developers continue to built.This study aim to analyze the factors which are presumed to influence the house purchaser to purchase a simple redisential house in Sematang Borang District. This research uses primary data with samples as much as 110 respondents. The research used logistic-regression as the analyzing tool. The estimation results indicate that the location of the house has a non-significant and positive effect effect; the price suitability has a significant and positive effect; while the housing facilities has a non-significant and negative effect toward the decision of the purchaser. The most dominant variable in influencing the purchaser decision is the price suitability, with 1,96 odds ratio, which means that the decision of purchasing the simple residential house is 1,96 times compared to not purchasing the simple residential house